The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14814/phy2.13981
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking promotes bladder cancer via increased platelet-activating factor

Abstract: Cigarette smoking is the number one risk factor for bladder cancer development and epidemiological data suggest that nearly half of all bladder cancer patients have a history of smoking. In addition to stimulating the growth of a primary tumor, it has been shown that there is a correlation between smoking and tumor metastasis. Platelet activating factor (PAF) is expressed on the cell surface of the activated endothelium and, through binding with the PAF‐receptor (PAF‐R), facilitates transendothelial migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Interestingly the kidneys are not the only organ in the renal system affected by PAF and its metabolism. In humans, it is thought that cigarette smoking leads to alterations in urethral cells that share similar histology to urethral cells of interstitial cystitis and bladder pain syndrome (IC/BPS) patients through an inflammatory pathway mediated by PAF [287]. Overall it is demonstrated that PAF signalling is upregulated in IC/BPS and that cigarette smoke exposure further upregulated this pathway [287].…”
Section: Current Trends In Platelet-activating Factor Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly the kidneys are not the only organ in the renal system affected by PAF and its metabolism. In humans, it is thought that cigarette smoking leads to alterations in urethral cells that share similar histology to urethral cells of interstitial cystitis and bladder pain syndrome (IC/BPS) patients through an inflammatory pathway mediated by PAF [287]. Overall it is demonstrated that PAF signalling is upregulated in IC/BPS and that cigarette smoke exposure further upregulated this pathway [287].…”
Section: Current Trends In Platelet-activating Factor Researchmentioning
confidence: 99%
“…In humans, it is thought that cigarette smoking leads to alterations in urethral cells that share similar histology to urethral cells of interstitial cystitis and bladder pain syndrome (IC/BPS) patients through an inflammatory pathway mediated by PAF [287]. Overall it is demonstrated that PAF signalling is upregulated in IC/BPS and that cigarette smoke exposure further upregulated this pathway [287]. Future research aims to determine the role of PAF in IC/BPS development, whether PAF can act as a marker of IC/BPS, and if PAF antagonists may have therapeutic value in IC/BPS [288].…”
Section: Current Trends In Platelet-activating Factor Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that cigarette smoke induces initiation and progression of bladder cancer, mediating EMT and activating ERK1/2 pathway. Kispert S. et al reported that the exposure of bladder cancer cells to cigarette smoke extract results in increased platelet-activating factor accumulation and increased expression of the platelet-activating factor receptor [ 62 ].…”
Section: Potential Effects Of Environmental Factors On Bladder Canmentioning
confidence: 99%
“…Tobacco smoking is a risk factor for the occurrence and increases the incidence of various cancers, including bladder [1], head and neck [2], lung [3], and pancreatic cancer [4]. Tobacco smoking contains many carcinogenic chemicals that can create a specific mutational signature and increase the somatic mutational burden associated with unrepaired DNA damage [5].…”
Section: Introductionmentioning
confidence: 99%